Protective cellular immunity generated by cross-presenting recombinant overlapping peptide proteins - Cai, L; Zhang, J; Zhu, R; Shi, W; Xia, X; Edwards, M; Finch, W; Coombs, A; Gao, J; Chen, K; Owen, S; Jiang, S; et al. (Impact Journals, 2017)
Priming of naive CD8+ and CD4+ T cells by dendritic cells (DCs) requires effective antigen presentation on both MHC class I and II molecules. We have developed a novel technology to use recombinant overlapping peptides (ROP) that stimulate both CD8+ and CD4+ T cell immune responses. The single chain protein of a ROP is made up of overlapping peptides linked by the target sequence (LRMK) for cathepsin S, a protease found in the endosomes of DCs. We designed synthetic genes encoding ROPs derived from ovalbumin (OVA), tuberculosis protein (CFP10-ESAT6), human papilloma virus (HPV) protein (E7) and survivin, a protein commonly over-expressed in tumour cells. An epitope from ROP-OVA was cross-presented and detected by a CD8+ T cell receptor-like antibody (TCR like Ab). Human DCs pulsed with ROP-survivin activated CD8+ T cells. CD4-low PBMCs from HIV and TB co-infected patients recognized ROP-CFP10-ESAT6 compared to a soluble form of the antigen. Immunization of mice with ROP-survivin or ROP-HPV-E7 generated specific cellular immune responses and protected mice from inoculation with melanoma B16 cells expressing survivin or HPV-E7 proteins. Together these data provide evidence to support ROP as a central component of a new platform for therapeutic vaccines and diagnostics.